A Study on Relapsed b-Cell Lymphoma in Elderly Patient of Bangladeshi Population with Rituximab, Gemcitabin and Oxaliplatin: an Effective Salvage Regimen (Anwer Khan Modern Medical College Journal, 2014)
High-dose therapy (HDT) with stem-cell support is the reference treatment for relapsed lymphoma, but is not appropriate for all patients. In Bangladesh High-dose therapy with stem cell support is not yet available. Conventional salvage chemotherapies have been used with limited efficacy and significant toxicity. Rituximab, gemcitabin and oxaliplatin are active as single agents in relapsed or refractory lymphoma, and have demonstrated synergistic effects in vitro and in vivo. Twenty two patients with relapsed or refractory or b-cell lymphoma received up to Six cycle of R-GemOx (rituximab 375mg/m2 on day 1, gemcitabine 1000mg/m2 and oxaliplatin 100mg/m2 on day 2). The majority (60%) had diffuse large b-cell lymphoma. After four cycle of R-GemOx, the overall response rate was 90% (45% complete response (CR)/unconfirmed CR (CRu). High CR/CRu rates were observed in all histological subtypes. In patients who had previously received rituximab, the CR/CRu rate after six cycles was 70%. The 2 year event-free and overall survival rates (median follow-up of 24 months) were 55%, respectively, among responders, the probability of being disease free for 2 years was 70%. Treatment was generally well tolerated. R-GemOx shows promising activity with acceptable toxicity in patients with relapsed/refractory b-cell lymphoma. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18838 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 29-34